Dynamic lot sizing model for retailers with multi suppliers, quantity discounts, and capacity constraints that consider advance demand informations - Rendiyatna Ferdian; Abdul Hakim Halim (International Journal of Production Management and Engineering)
The Dynamic lot sizing (DLS) model is widely used in production planning, to minimize inventory levels, which basically will minimize production costs. The DLS model tries to eliminate the assumption of a fixed demand level throughout the period used in the Economic Order Quantity (EOQ) model. The characteristics of business processes in online retailers are the basis of this research to develop DLS models. This research develops a DLS model for retailers with multi-supplier cases, quantity discounts, and capacity constraints that consider Advanced Demand Information (ADI). Based on the numerical test results, it appears that ADI has an effect on reducing total production costs in the DLS model. The results of the numerical tests also showed that the model was able to solve the problems of the production planning process for SMEs and retailers who considered ADI.